Organizaciones privadas del sector salud de maracaibo: estrategias financieras y ventajas competitivas - Borjas, Carlos (2008)
The objective of the research was to analyze the financial strategies for developing competitive advantages in the private health sector organizations in Maracaibo, Venezuela, through a descriptive methodology that required documental analysis and the application of a survey as tool for data collection, to the financial managers of the health centres of the city. A trend was found in the financial strategies of giving importance to the generation of business value and shareholder value, as well as a dual type of internal-external funding that positively affect the development of competitive advantages that allow them to face the dynamism imposed by the context.